A NEW SPECIES OF ETLINGERA (ZINGIBERACEAE) FROM BOUGAINVILLE ISLAND, PAPUA NEW GUINEA - Poulsen, A. D.; Bau, B. B. (Edinburgh Journal of Botany, 2017)
A new species, Etlingera frederikii, is described and illustrated, and is the first record of the genus in the Bougainville Region. Etlingera frederikii and E. cevuga, which occurs in Fiji and Samoa, are the two most easterly species in the distribution range of the genus. The new species differs from Etlingera cevuga in its much larger leaves, with a conspicuously silky-haired band on the ligule; the smaller, narrowly ovoid to cylindrical inflorescence with pale brown bracts (not hemiglobose with reddish brown bracts); and fewer, smaller flowers.
Keywords: Alpinieae; Amomum cevuga; ginger; IUCN; New Guinea; taxonomy; Western Pacific